MATHEMATICAL MODELING OF THE DYNAMICS OF TRANSFER PROCESSES DEHYDRATION AND GRANULATION IN A FLUIDIZED BED - Корнієнко, Б.Я. (Proceedings of National Aviation University (archive), 2012)
An approach to the description of multivariate process of dehydration and granulation in a fluidized bed, which is accompanied by a phase transition is complicated by the formation of liquid phase on the surface of the pellet, followed by removal of the liquid phase and the formation of a mass crystallization by a layer of microcrystals. Presents a mathematical model of two-phase Euler-Euler.